O professor diante do fracasso escolar: um estudo de caso da ideologia docente - Ferrarez, Silvana Tavares (2009)
From the case study of a unit of public education, this research aimed to investigate the existence of ideological mechanisms of professoriate speech about the school failure of the less advantaged social stratum, in order to captivate some of the strategies put in action by teachers to avoid any responsibility that may reflect on them as the low academic achievement of students. Based on the connection between the valuing of the cultural capital and the selection process played by the school system within the capitalist model and having as the main theoretical references the authors Pierre Bourdieu & Jean Claude Passeron and Christian Baudelot & Roger Establet, who comment upon the education system, we set out to verify the participation of professor as an agent of social education system, which contributed to the reproduction of social relations, trying to analyze how teachers recognized themselves through the success or failure of their school student and ideological mechanisms diffused by them to hide their contribution in the process production of school failure, in particular, concerning students from underprivileged social classes, which are often labeled and stigmatized as losers or unable, for failing to be successful in school activities.(AU)